2010
DOI: 10.1016/j.yexcr.2010.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The C/EBPbeta isoform, liver-inhibitory protein (LIP), induces autophagy in breast cancer cell lines

Abstract: Autophagy is a process involving the bulk degradation of cellular components in the cytoplasm via the lysosomal degradation pathway. Autophagy manifests a protective role in stressful conditions such as nutrient or growth factor depletion; however, extensive degradation of regulatory molecules or organelles essential for survival can lead to the demise of the cell, or autophagy-mediated cell death. The role of autophagy in cancer is complex with roles in both tumor suppression and tumor promotion proposed.Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Since LIP has been found to be regulated by the ER stress response program 15 and can regulate stress-triggered processes, 16,17 we examined the effect of ectopically expressed LIP on T-Ag expression levels. As shown in Figure 2A, transfecting increasing amounts LIP expression plasmid into BsB8 cells caused a progressive decline in T-Ag expression.…”
Section: Treatment With Thapsigargin Induces Lip and Downregulates Jcmentioning
confidence: 99%
See 1 more Smart Citation
“…Since LIP has been found to be regulated by the ER stress response program 15 and can regulate stress-triggered processes, 16,17 we examined the effect of ectopically expressed LIP on T-Ag expression levels. As shown in Figure 2A, transfecting increasing amounts LIP expression plasmid into BsB8 cells caused a progressive decline in T-Ag expression.…”
Section: Treatment With Thapsigargin Induces Lip and Downregulates Jcmentioning
confidence: 99%
“…14 LIP has been found to be regulated by the stress response program induced by ER stress 15 and LIP regulates stress-triggered cell death 16 and autophagy. 17 In the present study, we examine the effect of C/EBPb LIP on JCV T-Ag.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemical inhibitors of autophagy also prevent the death of cancer cells induced by a variety of agents [17] . This opposite role of autophagy as an executioner of cell death [18][19][20] and, thus, playing a role as a tumor suppressor [11] , could probably be explained by a persistent degradation of components essential for cell survival [4,21] . Therefore, it appears that, in addition to its conventional role in cell survival, autophagy can be also a death-promoter, in particular when the stimulus is too intense, when autophagy is extensive, or under conditions of inhibition of apoptosis.…”
Section: Role Of Autophagy In Survival and Death Of Tumor Cells In Rementioning
confidence: 99%
“…Thus, there is a form of cell death, whose main feature is the appearance of abundant autophagic vacuoles in the cytoplasm of dying cells, known as autophagic or type Ⅱ cell death, and several of its characteristics, based mainly on morphological criteria, have been described in recent years [20] . Type Ⅱ cell death would occur because of persistent autophagy with excessive degradation of cell components essential for survival [4,21] , and it is usually accompanied by inhibition of the phosphatidylinositol 3-kinase/protein kinase B/ mammalian target of rapamycin (PI3kinase/Akt/mTOR) signaling pathway [37,38] , which is the main regulator of autophagy, and by increased levels of LC3-Ⅱ [1] , a protein that is recruited to autophagosomes and that, under certain conditions, can be used as a reliable marker for autophagy [39,40] . However, different studies have found that some of the apoptotic cell death features cited above are also associated with an increased autophagy [18,29] .…”
Section: Autophagy In the Context Of Cell Deathmentioning
confidence: 99%
“…REPA's predictions associated 58 TFs with the gene sets identified as differentially expressed in the breast cancer expression profiling study. Out of these 58 TFs, 50 (or 86%) have previously been directly linked to breast cancer; namely, AP2ALPHA [85], AP2GAMMA [85], ATF1 [86], ATF2 [87], ATF3 [88], BAF155 [89], BCL3 [90], BCLAF1 [91], BHLHE40 [92], [93], BRCA1 [94], CBX3 [95], CEBPB [96], CJUN [97], COREST [98], CREB1 [99], E2F4 [100], E2F6 [61], EBF [101], ELF1 [102], ELK1 [103], ETS1 [104], FOXM1 [105], GABP [106], GR [107], HEY1 [108], IKZF1 [109], INI1 [110], KAP1 [111], MAX [112], MBD4 [113], MTA3 [114], MXI1 [115], MYBL2 [116], NFATC1 [117], NFIC [118], NRSF [119], PAX5 [120], PML [121], POL2 [122] RUNX3 [123], SMC3 [124], SP1 [125], SP4 [126], STAT3 [127], STAT5A …”
Section: Differentially Expressed Gene Sets Repa's Predicted Putativementioning
confidence: 99%